Risk factors associated with low back pain in rowers: a systematic review and meta-analysis - Ze, X.; Zhang, S.; Long, X.; Zhou, P. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Low back pain (LBP) is a prevalent injury among rowers, impacting their careers and potentially causing disability. However, the risk factors for LBP in rowers are still unclear, with most existing studies focusing on individual factors and lacking comprehensive meta-analyses.